Morphosemantic relations between verbs in Croatian WordNet - Šojat, Krešimir; Srebačić, Matea (2014)
This paper deals with morphosemantic relations between Croatian verbs and discusses their inclusion in Croatian WordNet. Morphosemantic relations refer to semantic relations between morphologically related verbs, i.e., between verbs from the same derivational family. A derivational family consists of verbs with the same lexical morpheme grouped around a base form. Generally, a verb with the simplest morphological structure serves as a base form for derivational processes. In Croatian, verbs are derived from base forms through prefixation and suffixation. Both derivational processes trigger aspectual and semantic changes. The focus is on semantic relations that regularly appear in various derivational families and consequently in various semantic fields. It is argued that these morphosemantic relations are crucial for the further development of Croatian WordNet.
Projekt MZOS
Projekt MZOS
ENG